Accuracy and repeatability of a semi-quantitative barefoot pressure measurement method for clinical use: The Derks Calculation Method. (June 2019) - Maetzler, M.; Bochdansky, T.; Abboud, R.J.
Highlights: The Derks Calculation Method is repeatable if the values for heel varus/valgus are excluded. The Derks Calculation Method was found to be accurate if the values for heel varus/valgus are excluded. The Derks Calculation Method is a viable tool when sophisticated computerised systems are not available. Abstract: Background: This study was designed to assess the accuracy and repeatability of the Derks Calculation Method in the normal foot during walking. Methods: Measurements were taken from 25 healthy subjects (age 32.0 ± 12.4), 23 females and 2 males, on five separate occasions at seven days, three weeks, three months, and nine months apart by means of a mid-gait method. Values were calculated for internal rotation (IR) and external rotation of the heel (ER), heel valgus/varus (HV), heel length (HL), heel width (HW), width of the midfoot (WM) and the forefoot (WF), and the length of the foot (LF). Results: For all five separate occasions and in 87.5% of the parameters investigated, the coefficient of repeatability (CR, expressed as a percentage of the mean) was less than 5%. One parameter showed a high CR - heel valgus/varus (HV) was extremely high (>800%). The maximum 95% Confidence Interval (CI) for the five different occasions was no higher than 0.2 cm for IR, ER and HV with a standard error (SE) of 0.01 and >0.01 respectively. The maximum 95% CI for WF was 0.4 cm (SE 0.1), and for HW, WM and LF the maximum 95% CI was 0.7 cm (SE 0.1 or 0.2). HL showed the highest 95% CI (0.9 cm) with an SE of 0.2. Conclusion: The Derks Calculation Method was found to be accurate and repeatable if HV was excluded, which renders this method a viable clinical tool in settings where sophisticated computerised systems are still unavailable.